Association of Inflammatory Factors with Cervical Cancer: A Bidirectional Mendelian Randomization - Li Q; Kaidong L; Tian Z; Diao W; Sun Y; Bai Y; Ma Y; Wei Y; Li J; Zhao W (Dove Medical Press, 2024)
Qi Li,1,2,* Liu Kaidong,3,* Zhiyu Tian,4 Weihua Diao,1,2 Yuhong Sun,1,2 Ying Bai,1,2 Yueyue Ma,4 Yimiao Wei,1,2 Jiarong Li,4 Weihong Zhao1,4 1Department of Obstetrics and Gynecology, The Second Hospital of Shanxi Medical University, Taiyuan, People's Republic of China; 2The Second Clinical Medical College, Shanxi Medical University, Taiyuan, People's Republic of China; 3Department of Radiation Oncology, Shanxi Provincial Cancer Hospital, Shanxi Hospital Affiliated to Cancer Hospital, Chinese Academy of Medical Sciences, Cancer Hospital Affiliated to Shanxi Medical University, Taiyuan, People's Republic of China; 4Department of Epidemiology, School of Public Health, Shanxi Medical University, Taiyuan, People's Republic of China*These authors contributed equally to this workCorrespondence: Weihong Zhao, Department of Obstetrics and Gynecology, The Second Hospital of Shanxi Medical University, No. 182 Wuyi Road, Taiyuan, 030001, People's Republic of China, Email sydeyzwh@sxmu.edu.cnPurpose: Persistent human papillomavirus infection is thought to be the main cause of the cervical cancer development along with inflammation. However, the potential mechanisms of action of the inflammatory factors in cervical cancer remain unclear. Therefore, this study aimed to assess the relationship between inflammatory factor levels and cervical cancer risk using a two-sample bidirectional Mendelian randomization (MR).Patients and Methods: MR utilizes single nucleotide polymorphisms as a tool to infer potential causal relationships between exposure factors and outcomes. Datasets for 91 inflammatory factors and cervical cancer were obtained from publicly available pooled data. The inverse variance weighted method was used as the main method and MR-Egger, weighted median, simple mode, and weighted mode were used as auxiliary analyses. Results were tested for robustness using sensitivity tests. In addition, we assessed the possibility of reverse causality between cervical cancer and the derived inflammatory factors by performing a reverse MR analysis. Finally, a preliminary experimental validation was performed.Results: We found that artemin and monocyte chemoattractant protein-4 levels were significantly correlated with elevated cervical cancer risk (β: 0.0024, P = 0.002 and β: 0.0010, P = 0.016, respectively. In contrast, interleukin-18 and interleukin-22 receptor subunit alpha-1 levels were associated with reduced risk of cervical cancer (β: − 0.0010, P = 0.029 and β: − 0.0021, P = 0.046, respectively). Sensitivity analyses were more robust as no significant heterogeneity or horizontal pleiotropy was observed.Conclusion: A significant causal relationship was found between the four inflammatory factors and the risk of cervical cancer, providing new evidence of their clinical implications in cervical cancer diagnosis and treatment.Keywords: ARTN, CCL13, cervical cancer, human papillomavirus, IL-18, IL-22RA1, inflammatory factors, Mendelian randomization